Holey barrier: claudins and the regulation of brain endothelial permeability - Matter, Karl (The Rockefeller University Press, 2003)
Endothelial tight junctions (TJs) are an important functional part of the blood-brain barrier (BBB). In this issue, Nitta et al. (2003) demonstrate that claudin-5, a transmembrane protein of TJs, is a critical determinant of BBB permeability in mice. Unexpectedly, knockout of claudin-5 did not result in a general breakdown of TJs but in a selective increase in paracellular permeability of small molecules. This suggests that the BBB can be manipulated to allow selective diffusion of small molecules and makes claudin-5 a possible target for the development of drugs for this purpose.